Molecular Design of Novel Protein-Degrading Therapeutics Agents Currently in Clinical Trial - Ela Kacin; Raj Nayan Sewduth (Pharmaceutics, 2025)
The landscape of clinical trials aimed at targeting specific proteins has experienced significant advancements, presenting promising opportunities for the development of effective therapeutics across a range of diseases. These trials focus on the investigation of modulation of protein functions, utilizing innovative technologies such as PROTACs (Proteolysis-Targeting Chimeras) and other protein degraders. These innovative approaches aim to address previously undruggable targets, enhancing the specificity and efficacy of treatments. The current landscape of clinical trials encompasses a diverse array of therapeutic areas, including oncology, autoimmune diseases, and neurological disorders. For instance, drugs like ARV-471 and ARV-110 are in advanced phases for treating metastatic breast cancer and prostate cancer, respectively, by targeting estrogen and androgen receptors. Early-phase trials explored the potential of targeting proteins like IKZF1/3 in multiple myeloma and IRAK4 in autoimmune diseases. The conducted trials not only emphasize the therapeutic potential of protein degradation but also highlight the challenges associated with bioavailability, stability, and delivery mechanisms. As these clinical trials advance, they possess the potential to transform treatment paradigms, providing renewed hope for patients facing complex and refractory conditions.